(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Introduction: The prevalence of Hepatitis in pregnant women is about 6.5 in Pakistan. The frequency of Hepatitis is 7%. Objective: To determine the association of certain risk factors for transmission of HCV infection in pregnant women Study Design: Case control study Setting: Obstetric and Gynaecology Department , Sir Gana Ram Hospital, Lahore Duration of Study: From 19th Dececmber 2008 to 18th June 2009 Material and Method: 580 patients selected from patients presented in Obstetrics and gynae unit-I and divided in to 290 Anti HCV positive cases and 290 Anti HCV negative control subjects. Detailed history regarding past surgery, blood transfusion, D&C by untrained hospital setting and injectables by untrained persons outside hospital setting, taken and entered on specially designed proforma. Results: 206 (71.03%) Anti HCV positive cases and 108 (37.24%) control subject has history of surgery in past while 84 (28.97) cases and 182 (62.76%) control subjects did not have any history of surgery in past. Odd ratio was 41.60(20.69%) cases and 36 (12.41%) control ssubjects received blood transfusion at least three months back while 230 (79.31%) cases and 254 (87.59%) control subjects did not receive any blood transfusion in past. Odd ratio was 1.84. 138(33.79%) cases and 65 (22.41%) control subjects had history of D&C while 152(66.21%) cases and 225(77.59%)control subjects did not have any history of D&C by untrained persons outside hospital setting. Odd ratio was 3.1. 160(55.17%) cases and 150 (51.72%) control subjects had history of injectables (drips / injections) at leas three months back by untrained persons outside hospital setting while 130 (44.83%) cases and 140 (48.28%) controls did not receive any injectables ( drips / injectons 0. Odd ratio was 1.15. Conclusion: Past surgical history and history of D&C were the most important risk factors for transmission of hepatitis C infection among pregnant women.